An Examination of Publication Trends in Borderline Personality: A Bibliometric Analysis - Safaria, Triantoro (Universitas Islam Indonesia, 2024)
In recent years, borderline personality disorder (BPD) is recognized as a severe mental health issue, generating significant research interest. Despite this recognition, a comprehensive analysis of trends and publications within the field has not been conducted. To address the gap, this research performed a bibliometric analysis to identify trends and contributed to publications on BPD. The Scopus database served as the reference, analyzing 672 files spanning from 2018 to 2021 through VOSviewer. As a result, the Journal of Personality Disorder became the leading publisher of BPD related articles, followed by the Journal of Personality Disorder: Theory, Research, and Treatment in second place, with the Journal of Affective Disorder securing third position. The United States became the country with the highest number of publications. However, it was crucial to acknowledge the limitations of the research, particularly the restriction of the search to a single database, potentially leading to the exclusion of relevant articles described elsewhere. After analyzing the keywords through the co-occurrence map, seven distinct cluster groups in the scientific landscape associated with BPD were identified.